74.6k views
23 votes
Simplify 9xºy-3 Write your answer using only positive exponents.

User Waldfee
by
5.4k points

1 Answer

3 votes

Answer:

we conclude that:


\:9x^0y^(-3)=(9)/(y^3)

Explanation:

Given the expression


9x^0y^(-3)

Apply exponent rule:
a^(-b)=(1)/(a^b)


\:9x^0y^(-3)=9\cdot \:(1)/(y^3)x^0

Apply rule:
a^0=1,\:a\\e \:0


=9\cdot \:1\cdot (1)/(y^3)

Multiply fractions:
a\cdot (b)/(c)=(a\:\cdot \:b)/(c)


=1\cdot (1\cdot \:9)/(y^3)

Refine


=(9)/(y^3)

Thus, we conclude that:


\:9x^0y^(-3)=(9)/(y^3)

User Maxhungry
by
5.5k points